CONTROL OVER THE EXAMINATION AND ASSESSMENT OF STUDENTS' WRITTEN AND COMMUNICATION SKILLS IN FOREIGN LANGUAGE DEVELOPMENT (Conference Zone, 2022)
Teaching foreign language communication in a communicative way requires a methodically different approach to solving a problem that can be referred to as a control problem but also as a "learning management problem". The problem of controlling the learning of foreign languages is still controversial and not fully studied among scientists. Therefore, we can say that the issues of improving control in the teaching of foreign languages, including German, have not lost their relevance to this day. In this article, opinions and comments are made on the procedures for controlling the correction and evaluation of written and communication skills of students in foreign language acquisition.